(untitled) (Eurasian Journal of Philology Science and Education, 2020)
The article deals with the issues of ethnological research of literary text. The insufficiency of the scientific research of this problem in the field of translation theory and practice determines the urgency of this study. The methods of ethnological analysis are discussed: 1) the biographical method, according to which the social and cultural facts of a particular ethnic group can be studied using biographical materials and events. The object of this analysis is a literary text created in the spirit of realism; 2) analysis of the text with the preparation of the “questionnaire” – an empirical study, with the help of which ethno-cultural characteristics, values, religion of the heroes of a literary text are revealed; 3) the method of researching the personality in the context of culture, which determines the components of which the image described by the realist writer consists of. It mainly analyzes the character’s speech behavior through which ethno-cultural peculiarities are determined. The scheme of studying literary texts, aimed at revealing the ethno-cultural information of the source text at the stage of the pre-translation analysis is proposed.The topicality of this research is determined by the need for improving the quality of translated works and elimination of errors in the translation of ethno-cultural elements that arise due to insufficient knowledge of extralinguistic factors. As an example, the literary originality of the style of A. Nurpeisov, the classic of Kazakh literature is considered and the writer’s trilogy «Blood and Sweat» is analyzed.